2014
DOI: 10.1097/scs.0b013e3182a2eb3c
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Parameters in Patients of Cleft Lip and Cleft Palate With Special Reference to Eosinophil Counts

Abstract: Many cleft lip and cleft palate patients show high eosinophil counts. Absolute eosinophil count was found to be a better parameter for assessment of eosinophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Silva et al (2018) evaluated the risk factors and comorbidities in Brazilians with orofacial clefts, and anemia was one of the most frequent conditions, corroborating the findings of this present study. Singhal et al (2014) analyzed the hematologic parameters in individuals with CL/P and found a high prevalence of anemia (81.62%). In the same way, Santos et al (2006) showed that anemia was prevalent in non-syndromic patients with CL/P from the same rehabilitation center of the present study, cleft lip and palate being the most common type of orofacial cleft (Santos et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al (2018) evaluated the risk factors and comorbidities in Brazilians with orofacial clefts, and anemia was one of the most frequent conditions, corroborating the findings of this present study. Singhal et al (2014) analyzed the hematologic parameters in individuals with CL/P and found a high prevalence of anemia (81.62%). In the same way, Santos et al (2006) showed that anemia was prevalent in non-syndromic patients with CL/P from the same rehabilitation center of the present study, cleft lip and palate being the most common type of orofacial cleft (Santos et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The cleft presence disturbs the suction mechanism, which may impair breastfeeding (Ninno et al, 2011). Consequently, the child may have malnutrition, anemia, and infections (Dalben et al, 2003; Singhal et al, 2014; Kaye et al, 2019). CL/P requires particular breastfeeding techniques to overcome difficulties such as choking, reflux, and lack of suction (Rocha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we noticed a possible link between cleft lip/palate and eosinophilia. Several researches have indicated that eosinophilia was seen in 20-25% of cleft lip/palate cases [14,15], but the evidences are not enough to verify their connection, so further studies are required to draw a clear conclusion. In the treatment of eosinophilia, the necessary therapy is removing causes.…”
Section: Eosinophiliamentioning
confidence: 99%
“…Anemia is a common condition among individuals with cleft lip and palate, with an observed preoperative prevalence of 81% [3]. Among systemic factors, anemia stands out as one that can disrupt tissue perfusion [1].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, cleft lip and palate patients often undergo surgery during the recommended iron supplementation period [4]. Despite these considerations, a consensus regarding the necessity of erythrocyte replacement in cleft lip and palate patients remains elusive, as does a clear consensus regarding the impact of pre-existing anemia on wound healing in these patients [3].…”
Section: Introductionmentioning
confidence: 99%